A new energy analysis tool for ground source heat pump systems - Michopoulos, Apostolos; Kyriakis, N. A. (My University, 2009)
A new tool, suitable for energy analysis of vertical ground source heat pump systems, is presented. The tool is based on analytical equations describing the heat exchanged with the ground, developed in Matlab® environment. The time step of the simulation can be freely chosen by the user (e.g. 1, 2 h etc.) and the calculation time required is very short. The heating and cooling loads of the building, at the afore mentioned time step, are needed as input, along with the thermophysical properties of the soil and of the ground heat exchanger, the operation characteristic curves of the system's heat pumps and the basic ground source heat exchanger dimensions. The results include the electricity consumption of the system and the heat absorbed from or rejected to the ground. The efficiency of the tool is verified through comparison with actual electricity consumption data collected from an existing large scale ground coupled heat pump installation over a three-year period.
Keywords: Ground heat exchanger simulation; Ground heat exchanger long term operation; GSHP system electricity consumption